Role of 18F-MD-PSMA PET/CT in initial stage of intermediate and high risk prostate cancer - YAN Yeqing; LIANG Sheng; YANG Bin; ZOU Renjian; MA Yufei; CAI Lisheng; WANG Hui; FU Hongliang (Shanghai Jiaotong Daxue xuebao. Yixue ban, 2023)
Objective·To evaluate the role of 18F-MD-PSMA PET/CT in the initial stage of patients with moderate and high risk prostate cancer (PCa).Methods·A total of 67 patients with moderate and high risk PCa who were treated in Xinhua Hospital, Shanghai Jiao Tong University School of Medicine from September 2017 to June 2022 were initially staged by 18F-MD-PSMA PET/CT. Conventional imaging (CI), including multi-parameter magnetic resonance imaging (mp-MRI) and bone scintigraphy (BS), were performed within two weeks before 18F-MD-PSMA PET/CT. Twenty-five patients underwent 18F-FDG PET/CT at the same time. The sensitivity (SEN), specificity (SPEC), positive predictive value (PPV), negative predictive value (NPV) and accuracy (ACU) of 18F-MD-PSMA PET/CT in the initial stage were evaluated, and the results were compared with those of 18F-FDG PET/CT, mp-MRI and BS. The consistency of 18F-MD-PSMA PET/CT and CI in terms of primary lesion, regional lymph node metastasis and bone metastasis was evaluated by Kappa consistency test refering to the postoperative pathological T and N staging results and bone metastasis results of clinical follow-up. Kappa coefficient was calculated and compared.Results·Of the 67 patients with PCa, 38 patients underwent radical prostatectomy and had completed pathological data, with 27 patients undergoing regional lymphadenectomy and 1 patient undergoing expanded pelvic lymphadenectomy at the same time. The pathological results were obtained as gold standard. The detection rates of mp-MRI and 18F-MD-PSMA PET/CT in diagnosing intrathecal lesions were both 100%. The SENs in diagnosing bilateral intralobular lesions were 26.3% and 63.2%, respctively; the SPECs were both 75.0%.The Kappa consistency test showed that the consistency of 18F-MD-PSMA PET/CT in diagnosis of extracapsular extension (EPE), seminal vesicle invasion (SVI), and bladder neck invasion (BNI) was higher than that of mp-MRI. Fisher′s exact test showed that there were no statistically significant differences in SEN (P=0.226, P=0.491) and SPEC (P=1.000, P=0.342) between the two methods for diagnosing EPE and SVI, as well as SEN (P=1.000) for diagnosing BNI. In terms of diagnosis of lymph node metastasis, based on the analysis of lymph node numbers, the consistency between 18F-MD-PSMA PET/CT and pathological results was higher than that of mp-MRI (Kappa coefficients of 0.555 and 0.137, respectively). Fisher′s exact test showed that there were no statistically significant differences in SEN and SPEC between the two examination methods (P=0.562, P=0.829). Based on the patients, the consistency between 18F-MD-PSMA PET/CT and pathological results was higher than that of mp-MRI (Kappa coefficients of 0.850 and 0.313, respectively). There was no statistically significant difference in SEN between the two methods (P=1.000). In terms of diagnosis of bone metastasis, based on the analysis of bone lesion numbers, the consistency between 18F-MD-PSMA PET/CT and clinical follow-up results was higher than that of BS (Kappa coefficients of 0.500 and 0.299, respectively). Fisher′s exact test showed that there was no statistically significant difference in SEN between the two methods (P=0.219). Based on the patients, the consistency between 18F-MD-PSMA PET/CT and clinical follow-up results was higher than that of BS (Kappa coefficients of 0.953 and 0.766, respectively). There was no statistically significant difference in SEN between the two methods (P=1.000). The risks of 21 patients (31.3%) were increased after 18F-MD-PSMA PET/CT detection, with 1 patient (1.5%) decreasing. The initial stage of 32 cases (47.8%) were changed after 18F-MD-PSMA PET/CT detection, with 27 cases (40.3%) upstaged and 5 cases (7.5%) downstaged.Conclusion·18F-MD-PSMA PET/CT is superior to CI in the diagnosis of bilateral intralobular lesions, EPE, SVI, regional lymph node metastasis and bone metastasis in intermediate and high risk PCa, and on this basis, the diagnosis of clinical stage and metastatic status of some patients has been changed.